In fact essays on writers and writing - Mallon, Thomas 1951- (Pantheon Books, 2001)
"In Fact gathers the best of Thomas Mallon's superb criticism from the past twenty-two years - essays that appeared in his GQ column, "Doubting Thomas," and in The New York Times Book Review, The American Scholar, The New Yorker, and Harper's, among other publications. Here are his evaluations of the work of contemporary writers such as Nicholson Baker, Peter Carey, Tom Wolfe, Don DeLillo, Joan Didion, and Robert Stone, and reassessments of such earlier twentieth-century figures as John O'Hara, Sinclair Lewis, Truman Capote, and Mary McCarthy. Mallon also considers an array of odd literary genres and phenomena - including book indexes, obituaries, plagiarism, cancelled checks, fan mail, and author tours.